(untitled) (Archives of Pediatrics of Uruguay, 2023)
Introduction: in March 2020, a Health Emergency was decreed in Uruguay when the first cases of the SARS-CoV-2 (COVID 19) infection were detected. Voluntary home confinement was one of the public health measures adopted in theto control the pandemic. Objectives: describe the effects of confinement on sleep, eating and exercise habits of adolescents assisted by private health providers in Montevideo and Canelones during the COVID-19 pandemic. Methodology: ad hoc, voluntary, anonymous, online and self-administered survey to adolescents of 12 to 19 years of age, users of CASMU, CRAMI, COMECA and Asociación Española HMOs, between June 1 and July 1, 2020. Validated questionnaires were applied to assess sleep, diet and exercise habits. Results: 465 adolescents were surveyed, 70.1% women and 48.2% in mid-adolescence. They reported having been connected to Internet and cell phone more than 6 hours a day, 58.3% and 42.4%, respectively. Coexistence during confinement was mostly pleasant. 76% reported sleeping less than 9 hours/day. They reported an appropriate consumption of fruit 6%, vegetables 5.8% and dairy 32.2%. The percentage of active adolescents fell from 30.7% before the pandemic to 19.7% during the pandemic. To the question, What is the first word that comes to mind when you hear about the COVID-19 pandemic? most gave negative responses. Conclusions: confinement measures were not linked to important problems regarding coexistence with relatives in this group of adolescents. We observed a worsening of the eating, exercise and sleep habits, which may favor the “obesogenic environment” and increase the risk of developing chronic non-communicable diseases. It is relevant to consider the negative impact of confinement and plan preventive measures aimed at mitigating its effects.